Transaction Processing System Analysis Using The Distribution Management System (DMS) Nexsoft Distribution 6 (ND6) - Isnawati Muslihah; Sofia Agustin Nastura (International Journal of Computer and Information System (IJCIS), 2020)
Distribution Management  system  (DMS)  is  an  application  that  manages almost  the  entire  processing  of  sales  orders, purchases, inventory management and financial accounting. The DMS application is only intended for specific types of distribution businesses than other types of businesses, which are at least able to provide a much higher level of functionality, specifically for the needs  of  distribution  companies.  This  research was  conducted  at  PT.  Succeed  which  is  a  food  distribution  company.  The  daily transaction processing  system at  this  company uses DMS Nexsoft Distribution 6  (ND6). NexSoft Distribution 6  (ND6)  is  the main operating  system  for  any  trading  business  in carrying  out  daily  activities. NexSoft  distribution  is  produced  by PT. Paramadaksa Teknologi Nusantara which is a company engaged in Information Technology (IT), which is headquartered in the Tangerang area.